Testing Specificity: Associations of Stress and Coping with Symptoms of Anxiety and Depression in Youth - Bettis, Alexandra H. (J Child Fam Stud, 2015)
Research has documented the co-occurrence of symptoms of anxiety and depression across the lifespan, suggesting that these symptoms share common correlates and etiology. The present study aimed to examine potential specific and/or transdiagnostic correlates of symptoms of anxiety and depression in at-risk youth. The present study examined youth stress associated with parental depression and youth coping as potential correlates of symptoms of anxiety and depression in a sample of children of depressed parents. One hundred eighty parents with a history of depression and their children ages 9–15 completed measures assessing youths’ stress associated with parental depression (RSQ), symptoms of anxiety and depression (YSR and CBCL), and coping (RSQ). The results support the hypothesis that secondary control coping is a transdiagnostic correlate of symptoms of anxiety and depression in youth. Youth stress related to parental depression and primary control coping were specific correlates of youth depressive symptoms and not anxiety symptoms. Disengagement coping was not a significant correlate of symptoms of anxiety or depression in youth. Results suggest that there are both transdiagnostic and specific correlates of symptoms of anxiety and depression in youth. The current study provides evidence to suggest specific types of stress and strategies to cope with this stress demonstrate specificity to symptoms of anxiety and depression in high-risk offspring of depressed parents. These findings highlight the importance of understanding the relationship between stress, coping, and symptoms to inform prevention and treatment research.